Vulnerability, beliefs, treatments and economic burden of chronic obstructive pulmonary disease in rural areas in China: a cross-sectional study - Lou Peian; Zhu Yanan; Chen Peipei; Zhang Pan; Yu Jiaxi; Zhang Ning; Chen Na; Zhang Lei; Wu Hongmin; Zhao Jing (BMC, 2012)
Abstract Background The incidence of chronic obstructive pulmonary disease (COPD) in China is very high. This study aimed to assess the vulnerability of COPD patients in rural areas outside Xuzhou City, Jiangsu province, in order to provide helpful guidance for future research and public policies. Methods The vulnerability of 8,217 COPD patients was evaluated using a face-to-face questionnaire to obtain information on general characteristics, awareness, beliefs, medication usage, acute exacerbation of the disease, and economic burdens. Direct economic burdens were calculated based on the questionnaire, and indirect economic burdens were estimated using local per capita income and life expectancy in 2008. The years of potential life lost were calculated using loss of life years for each age group and multiplying by the number of deaths in a given age group. Results Of the 8,217 patients, 7,921 (96.4%) had not heard of COPD, and 2,638 (32.1%) did not understand that smoking was a risk factor for COPD. No patients had used inhalers, nebulizer drugs or oxygen therapy, either regularly or sporadically. No patients had undergone pulmonary rehabilitation or surgical treatment, while 4,215 (51.3%) took theophylline to relieve dyspnea, and 3,418 (41.6%) used antibiotics to treat exacerbations. A total of 2,925 (35.6%) patients had been admitted to hospital during the past year because of respiratory symptoms. The average direct and indirect economic burdens on COPD patients were 1,090 and 20,605 yuan, respectively. Conclusions The vulnerability of patients in rural Xuzhou to COPD was high. Their awareness of COPD was poor, their treatment during both the stable and acute exacerbation stages did not meet standards, and the economic burdens were large. Interventions are therefore needed to improve the prevention and management of COPD in this population. Further studies are required to verify these findings.